The Life and Times of Ceaușescu Jokes - Gabriela Glăvan (Metacritic Journal for Comparative Studies and Theory, 2019)
Political humour, as an indispensable part of popular culture, played a complex role under communism in Romania. It was a catalyst of the general discontent towards the catastrophic effects of Ceaușescu’s megalomaniac dictatorship, a forbidden, dangerous means of expressing opposition. This dynamic part of folklore captured and exposed essential aspects of life in communism, from the permanent fear of the Securitate to the ever-growing ridicule of the presidential couple and their acolytes. Unforgiving jokes targeting the Ceaușescus, now almost forgotten, rendered the grotesque portraits of the abusive, illiterate leaders of a totalitarian regime, radically contrasting with the official discourse that glorified them as heroes of socialism and parents of the nation. Drawing from a rich body of theoretical approaches to political humour and, particularly, political folklore, I intend to critically reread Romanian political humour of the communist era regarding Nicolae and Elena Ceaușescu in order to question its role in transforming the public perception of autocratic power. Authors such as Egon Larsen, Dana Maria Nicolescu Grasso, Christie Davies and Eliott Oring, among others, have closely explored the complex territory of this limited yet significant cultural realm. I also intend to explore its specific traits as a potentially particular genre and re- evaluate some divergent theoretical stances that view gallows humour in a dictatorial regime either as a concrete protest or as a means of rerouting and defusing resentment. The creative richness of this rather dominant part of Romanian political humour of the 70s and 80s could reveal a unique territory in which caricature is nurtured by everyday despair.